The Influence Of Leadership And Work Environment On Employee Performance Atma Jaya University - Apriliana, Putri Salsabila; Febriyantoro, Mohamad Trio (PERFECT EDUCATION FAIRY, 2023)
This study aims to determine the effect of leadership and work environment on employee performance at Atma Jaya University. This type of research uses qualitative research methods with 30 employees as research respondents. The sampling technique uses the google form and is tested for validity and reliability. This study uses multiple linear regression analysis using SPSS 23 software. The results of this study are that leadership has a positive but not significant effect on employee performance and work environment has a positive but not significant effect on employee performance.